Analyzing the future security of bkash money transaction occurring due to money laundering and financing terrorism - Haque, Shahareen Mehjabin (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.